Allergies: from stress to psychosomatic diseases - Snežana Medenica; Milan Stojaković; Bogdan Zrnić; Goran Vasić; Verica Prodanović; Helena Marić Kujundžić (Биомедицинска истраживања, 2010)
Holistic approach to the nature of human beings shows the view of the man as a unique and indivisible whole and not as a collection of organs that are not interconnected. This means the integrity of the biological, psychological and social nature of the man and that just means the psychosomatic approach to the disease. More and more studies indicate that psychological stress can aggravate or improve some allergic diseases. Today there are a lot of discussions about the effects of chronic stress which has lasted for years and decades. Many unpleasant events from the past, such as fear, aggressive wishes, guilt and others, can have its effect on the body systems later, and gradually cause functional disorders and organic diseases within them. Enhanced work of the nervous system and increased secretion of hormones, which can protect us when the stress occurs for the first time, represents the same changes which can destroy us in the end when we face constant and persistent stress. Some studies have shown that in addition to heredity, common infections of the respiratory tract and pollution of the environment are the main villains for the development of allergic diseases as well as stress. Recent studies emphasize that stress and anxiety can extend the duration of seasonal allergies and boost their symptoms.
Keywords: psychoneuroimmunology; neuroimmune; neuroimmunology; stress; immunity; allergy; asthma and inflammation